Landscape Functionality Analysis of Soil Surface Conditions in an Arid Zone: A Case Study of Lajaneh Piosphere, Iran - Shahriary, Eahsan; S, Shubhasmita; Langford, P (Annals of Arid Zone, 2019)
Livestock grazing changes landscape functionality, nutrient availability and soil structure and surface conditions in dryland rangelands. A piosphere is a zone of interaction among vegetation, watering point and livestock. This study uses landscape and soil indicators to evaluate the condition of the soil surface in Lajaneh piosphere, Shahrood, Iran. Lajaneh is in an arid region, with predominant land cover of Zygophyllum eurypterum, and grazed by camels, goats and sheep. We used landscape function analysis (LFA) and trigger-transfer-reserve-pulse (TTRP) to derive eleven soil surface indicators which were measured and combined to calculate the three indices of infiltration, stability and nutrient cycling. One-way ANOVA and Tukeyâ€™s post hoc tests were used to find the differences in infiltration, stability and nutrient cycling indicators among three distances 10, 100 and 1000 m. Significant differences were found in infiltration, stability and nutrient cycling among at 10 m, 100 m and 1000 m from watering point. The three indices of nutrient cycling, infiltration and stability increased with increasing distance from watering point. Our study showed the importance of vegetation patches and runoff/runon processes in soil surface condition, and showed the results of grazing pressure on soil health centered on the â€œsacrifice zoneâ€ closest to the watering point and decreasing with distance. We show that the LFA method is an effective measure for monitoring soil surface health around watering points and piosphere, balancing the feedbacks and offtakes based on the condition of soil surface indices. Key words: LFA, piosphere, arid zone, overgrazing, offtakes, feedbacks